Karakteristik Morfometri, Fisiologi, Hematologi dan Kimia Darah Owa Jawa (Hylobates moloch) di Penangkaran Pusat Studi Satwa Primata–IPB - Permana wati; Y. Fitrianis; Lila .; Y. Paramastri; I Nengah Budiarsa; Joko Pamungkas (Jurnal Primatologi Indonesia, 2009)
The aim of this study was to provide information on morphometrical, physiological, hematological and blood chemical values data of Javan Silvery Gibbon (Hylobates moloch). These data were collected from one family in captive breeding at the Primate Research Center of Bogor Agricultural University. The family consisted of one adult male, and female, including their  three offspring (2 females and 1 male). There was no previous publication reference available for Hylobates moloch.  In comparison to other different species within the same genus of Hylobates, there were difference in hematologic and serum biochemical values between Hylobates moloch and Hylobates lar. Keywords: morphological, physiological, hematological, blood-chemical values, Hylobates moloch.